2018
DOI: 10.1002/anie.201801250
|View full text |Cite
|
Sign up to set email alerts
|

Combined In Situ Illumination‐NMR‐UV/Vis Spectroscopy: A New Mechanistic Tool in Photochemistry

Abstract: Synthetic applications in photochemistry are booming. Despite great progress in the development of new reactions, mechanistic investigations are still challenging. Therefore, we present a fully automated in situ combination of NMR spectroscopy, UV/Vis spectroscopy, and illumination to allow simultaneous and time‐resolved detection of paramagnetic and diamagnetic species. This optical fiber‐based setup enables the first acquisition of combined UV/Vis and NMR spectra in photocatalysis, as demonstrated on a conPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 57 publications
1
56
0
3
Order By: Relevance
“…Hence, in a consecutive mechanism, overlap between the emission spectrum of the light source (dotted lines in Figure c) with the absorption of the species that absorbs the second photon is always more important. Recording a photo‐action spectrum is a somewhat laborious experiment, which might become easier in the future with wavelength‐tunable LEDs and on‐line photoproduct detection …”
Section: Kinetic Aspects and Pertinent Methods In Multi‐photon Excitamentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in a consecutive mechanism, overlap between the emission spectrum of the light source (dotted lines in Figure c) with the absorption of the species that absorbs the second photon is always more important. Recording a photo‐action spectrum is a somewhat laborious experiment, which might become easier in the future with wavelength‐tunable LEDs and on‐line photoproduct detection …”
Section: Kinetic Aspects and Pertinent Methods In Multi‐photon Excitamentioning
confidence: 99%
“…Using the reduction of 4′‐bromoacetophenone as a model reaction, the mechanistic study found that the onset of acetophenone formation correlated with PDI .− degradation, and the conclusion was that this reaction takes place through an unidentified photo‐decomposition product of PDI . Using the less challenging substrate 4‐bromobenzaldehyde instead of 4′‐bromoacetophenone, a combined NMR and UV/Vis study with in‐situ photo‐irradiation found no clear correlation between PDI .− degradation and product formation, and the mechanism of Figure seems to operate …”
Section: The Next Level: Reductive Excited‐state Quenching Followed Bmentioning
confidence: 99%
“…[72] NMR spectroscopy can also be used to detect the formation of radicals during photochemical reactions using Chemical Induced Dynamic Nuclear Polarization (CIDNP) spectroscopy. [73] This technique can detect the "signatures" left by short-lived radical pairs in the nuclei of the downstream diamagnetic species,which are detectable by simple 1 HNMR analysis in the form of enhanced absorption and emission peaks.T his method is independent of the radical lifetimes,and short-lived open shell species are detectable in the minute timescale.G enerally,aphoto-CIDNP experiment requires in situ illumination within the NMR spectrometer.E asily assembled LED-based devices, which can be used to provide high photon flux directly in the NMR tubes,h ave been reported [74] and used to elucidate photochemical reaction mechanisms. [75] Thed etection of highly elusive intermediates,i ncluding non-radical ones,r equires more sensitive time-resolved spectroscopic techniques, [76] such as laser flash photolysis (LFP).…”
Section: Detection Of Reaction Intermediatesmentioning
confidence: 99%
“…Daher ist eine Überlappung zwischen den Wellenlängen des Anregungslichts (gestrichelte Linien in Abbildung c) und der Spezies, die das zweite Photon absorbiert, für konsekutive Mechanismen von größerer Bedeutung. Das Messen eines Photoaktionsspektrums ist zeitaufwendig, allerdings könnte dies in Zukunft durch LEDs mit verstellbarer Wellenlänge und Methoden zur direkten Photoproduktdetektion einfacher werden …”
Section: Kinetische Aspekte Und Relevante Methoden Für Multiphotonen‐unclassified
“…Mit dem weniger anspruchsvollen 4‐Brombenzaldehyd als Substrat wurde während der In‐situ‐Bestrahlung mit NMR‐ und UV/Vis‐Analytik keine klare Korrelation zwischen PDI‐Zersetzung und Produktbildung gefunden. In diesem Fall scheint der Mechanismus von Abbildung abzulaufen …”
Section: Die Nächste Ebene: Reduktives Löschen Angeregter Zustände Gunclassified